EVALUASI KINERJA UNIVERSITAS ANDALAS BERDASARKAN INDIKATOR SATUAN KERJA BADAN LAYANAN UMUM BIDANG LAYANAN PENDIDIKAN - MISNELI MISNELI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2018)
In the performance assessment of BLU for public universities in 2012 conducted by Kemdikbud, there are 24 educational institutions with the status of Public Service Board including those of Andalas University with BLU status in 2009 with rank 14 of 24 educational institutions. Based on the decision, the researcher is interested in assessing the performance of BLU Unand in 2014 and evaluating the constraints faced against unachieved performance as well as evaluation of the target or performance score of the BLU work unit indicator itself as well as the recommendations given. The method of this research is using mixed methode (combination between quantitative and qualitative). The research process begins by taking research data, processing data, interviews and final results. The results of this study indicate that the performance of BLU Unand in 2014 is good with the predicate A with a score of 74.3. By 2014 Unand's performance if judged by the BLU indicator is not satisfactory because the highest score is excellent with the AAA predicate and the total score is more than 95. There are several targets of indicators that have not been reached in the financial aspects ie cash ratio, current ratio, asset turnover fixed income, equity compensation, income ratio of PNPB to operational cost, definitive RBA, financial report based on SAK, Statement of Income Rule and Expenditure BLU, SOP of receivable management and debt management SOP. Meanwhile, if viewed from the aspects of service that has not been achieved is the accreditation, achievement and customer satisfaction.